1988
DOI: 10.1002/j.1834-4453.1988.tb00188.x
|View full text |Cite
|
Sign up to set email alerts
|

A cache of tulas from the Boulia district, western Queensland

Abstract: The excavation and analysis of fifty stone artefacts found in a prehistoric pit on Mucklandama Creek, in western Queensland is described. These artefacts provide information on the manufacture. of tulas and on the differentiation of unused and exhausted tulas. It is argued that the feature recovered from Mucklandama Creek is a cache of unused tulas destined for barter. A radiocarbon date demonstrates that the cache is less than 1000 years old. A review of data from other parts of Australia reveals that similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 17 publications
4
19
0
Order By: Relevance
“…This variation resonates with the ethnographies that suggested the curvature of the working edge determined the flake's primary application and, accordingly, the depth and width of the incision made. The extent of retouch exhibited on the tulas is also in direct accordance with ethnographic observation and archaeological research into tula reduction (Hiscock 1988;Roth 1904). However, apart from the distal edge retouch evident on the slugs, Archaeological science under a microscope: studies in residue and ancient DNA analysis in honour of Thomas H. Loy Archaeological science under a microscope: studies in residue and ancient DNA analysis in honour of Thomas H. Loy it was difficult to conclude with any certainty which scarring was produced through manufacture or as a result of use.…”
Section: Use-wearsupporting
confidence: 75%
“…This variation resonates with the ethnographies that suggested the curvature of the working edge determined the flake's primary application and, accordingly, the depth and width of the incision made. The extent of retouch exhibited on the tulas is also in direct accordance with ethnographic observation and archaeological research into tula reduction (Hiscock 1988;Roth 1904). However, apart from the distal edge retouch evident on the slugs, Archaeological science under a microscope: studies in residue and ancient DNA analysis in honour of Thomas H. Loy Archaeological science under a microscope: studies in residue and ancient DNA analysis in honour of Thomas H. Loy it was difficult to conclude with any certainty which scarring was produced through manufacture or as a result of use.…”
Section: Use-wearsupporting
confidence: 75%
“…Roth (1904 : 17) also noted that the platform was thinned on the dorsal surface prior to being hafted. Hiscock (1988) has provided evidence to support these observations from the Mucklandama Creek 6 cache, also in western Queensland, which contained 50 artifacts that were interpreted to be unused tula flakes at different stages of preparation. In particular, this analysis confirmed that platform thinning was a part of the retouching process and that the resulting "overhang removal" scars (Hiscock 1988 : 63-65) were not a remnant of platform preparation prior to flake detachment (cf.…”
Section: Manufacturing the Adhesive -supporting
confidence: 58%
“…Nevertheless, most of the evidence indicates that tula flakes are usually quite standardized in their dimensions, especially within the context of individual sites. A good demonstration of this comes from the data provided by Hiscock (1988) from the Mucklandama Creek 6 cache and nearby surface artifacts.…”
Section: Manufacturing the Adhesive -mentioning
confidence: 99%
“…The Bora radiocarbon chronology shows repeated use of the Rupert Creek area since at least 2000 BP. A cache of tula adzes near Boulia with a midHolocene date (Hiscock 1988) provides evidence that Aboriginal use of the wider MGD plains is indeed older. Unlike hearths, middens are rarely reported archaeologically -to 1990 only one midden site had been recorded in the MGD (Border and Rowland 1990:56).…”
Section: Discussionmentioning
confidence: 94%